2008
DOI: 10.3945/jn.108.095554
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acids from Green Coffee Extract are Highly Bioavailable in Humans

Abstract: Chlorogenic acids (CGA) are cinnamic acid derivatives with biological effects mostly related to their antioxidant and antiinflammatory activities. Caffeoylquinic acids (CQA) and dicaffeoylquinic acids (diCQA) are the main CGA found in nature. Because green coffee is a major source of CGA, it has been used for production of nutraceuticals. However, data on the bioavailability of CGA from green coffee in humans are inexistent. The present study evaluated the pharmacokinetic profile and apparent bioavailability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
395
5
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(435 citation statements)
references
References 44 publications
18
395
5
17
Order By: Relevance
“…Recently, Farah et al (2008) and Monteiro et al (2007) demonstrated for the first time that main isomers of CGA 3, are bioavailable in the human body. These results indicated that a small percentage of CGA ingested are absorbed in stomach, been the major part absorbed and metabolized in the small intestine.…”
Section: Metabolism Absorption and Bioavailability Of Hydroxycinnamimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Farah et al (2008) and Monteiro et al (2007) demonstrated for the first time that main isomers of CGA 3, are bioavailable in the human body. These results indicated that a small percentage of CGA ingested are absorbed in stomach, been the major part absorbed and metabolized in the small intestine.…”
Section: Metabolism Absorption and Bioavailability Of Hydroxycinnamimentioning
confidence: 99%
“…(diCQA), with at least 3 isomers per subclasses (Farah, Monteiro, Donangelo & Lafay, 2008;Monteiro, Farah, Perrone, Trugo, & Donangelo, 2007;Farah & Donangelo, 2006). CGA is found in many types of fruits (such as apples, blueberries, cherries, kiwis and plums), vegetables (chicory, potato and artichoke) and herbs (Ilex paraguariensis and Achyrocline satureioides), being coffee the main source in the Western diet (Marques & Farah, 2009;Manach et al, 2004;Clifford, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This provides some explanation for the non-313 detection in plasma; however, the possibility remains that CHL become degraded during sample treatment 314 process [37]. A study [38] evaluating the pharmacokinetic profile and bioavailability of CHL in plasma and 315 urine of 10 healthy participants showed a great deal of inter-individual variation in CHL absorption, metabolism…”
mentioning
confidence: 99%
“…Cholorogenic acids have high bioavailability in humans [30,31]. Because of the synergistic effect between caffeine and cholorogenic acid in green coffee extract, green coffee extract was shown to suppress body weight gain better than cholorogenic acid or caffeine alone [32,33].…”
Section: How Does Green Coffee Extract Work For Weight Loss?mentioning
confidence: 99%